2019
DOI: 10.2147/cmar.s210076
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA 145 enhances chemosensitivity of glioblastoma stem cells to demethoxycurcumin</p>

Abstract: Background: The presence of glioma stem cells (GSCs) is thought to be a key factor responsible for development of the incurable glioblastoma multiforme (GBM). GSCs are often displayed during chemotherapy resistance, except for demethoxycurcumin (DMC), a component of curcumin, which has been previously confirmed to inhibit GSCs proliferation and induce apoptosis. Purpose: The objective of this study was to identify the main mechanism underlying anti-GSCs resistance by DMC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…MiR‐145 enhanced chemosensitivity to demethoxycurcumin by targeting the SOX2‐Wnt/β‐catenin axis in glioma. SOX2, a pluripotent stem cell marker, plays a pivotal role in maintaining the undifferentiated situation and proliferation of stem cells 12 . CREB‐binding protein (CBP) is a Wnt signaling component, and is frequently activated in nasopharyngeal carcinoma.…”
Section: Mir‐145 In Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐145 enhanced chemosensitivity to demethoxycurcumin by targeting the SOX2‐Wnt/β‐catenin axis in glioma. SOX2, a pluripotent stem cell marker, plays a pivotal role in maintaining the undifferentiated situation and proliferation of stem cells 12 . CREB‐binding protein (CBP) is a Wnt signaling component, and is frequently activated in nasopharyngeal carcinoma.…”
Section: Mir‐145 In Drug Resistancementioning
confidence: 99%
“…Researchers are currently attempting to explore the target genes of miR‐145 and their signaling pathways involved in altering therapeutic response, which is significant for the development of miRNA‐related therapies. Strikingly, various research has disclosed that miR‐145 acts in reversion of therapeutic resistance in multiple tumors, including lung cancer, 3‐6 esophageal squamous cell carcinoma (ESCC), 7‐9 ovarian carcinoma, 10,11 glioma, 12,13 hepatocellular carcinoma (HCC), 14‐16 breast cancer, 17 colorectal cancer (CRC) 18‐21 prostate cancer, 22,23 bladder cancer, 24 gastric cancer (GC), 25,26 pancreatic adenocarcinoma 27 and cervical cancer 28,29 …”
Section: Introductionmentioning
confidence: 99%
“…The regulation of CSCs is a complex process, involving a variety of signaling pathways, such as the Wnt/b-catenin, Notch, transforming growth factor (TGF)b, and interleukin (IL)-6/STAT3 signaling pathways. Previous studies have shown that miR-145 can enhance the chemosensitivity of glioma stem cells to demethoxycurcumin 16 and regulate the epithelial-mesenchymal transition (EMT) process in osteosarcoma. 17 Additionally, lncRNA Linc-DYNC2H1-4 promotes CSC phenotypes by acting as a sponge of miR-145 in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR-145 is expressed at very low levels in GSCs, which is associated with increased tumorigenesis. Though, when experimentally induced, it increases U87 GSC apoptosis by inhibiting BNIP3 and Notch signaling [ 125 , 126 ]. Moreover, targeting of SRY-box transcription factor 9 ( SOX9 ) and adducin 3 ( ADD3 ) by miR-145 has been reported, consistent with increased apoptosis [ 127 ].…”
Section: Mirnas Involved In the Regulation Of Apoptosis In Human Nmentioning
confidence: 99%